Senecavirus A 3C Protease Mediates Host Cell Apoptosis Late in Infection - Maureen H. V. Fernandes; Mayara F. Maggioli; Jaelin Otta; Lok R. Joshi; Steve Lawson; Diego G. Diel (Frontiers in Immunology, 2019)
Senecavirus A (SVA), an oncolytic picornavirus used for cancer treatment in humans, has recently emerged as a vesicular disease (VD)-causing agent in swine worldwide. Notably, SVA-induced VD is indistinguishable from foot-and-mouth disease (FMD) and other high-consequence VDs of pigs. Here we investigated the role of apoptosis on infection and replication of SVA. Given the critical role of the nuclear factor-kappa B (NF-κB) signaling pathway on modulation of cell death, we first assessed activation of NF-κB during SVA infection. Results here show that while early during infection SVA induces activation of NF-κB, as evidenced by nuclear translocation of NF-κB-p65 and NF-κB-mediated transcription, late in infection a cleaved product corresponding to the C-terminus of NF-κB-p65 is detected in infected cells, resulting in lower NF-κB transcriptional activity. Additionally, we assessed the potential role of SVA 3C protease (3Cpro) in SVA-induced host-cell apoptosis and cleavage of NF-κB-p65. Transient expression of SVA 3Cpro was associated with cleavage of NF-κB-p65 and Poly (ADP-ribose) polymerase (PARP), suggesting its involvement in virus-induced apoptosis. Most importantly, we showed that while cleavage of NF-κB-p65 is secondary to caspase activation, the proteolytic activity of SVA 3Cpro is essential for induction of apoptosis. Experiments using the pan-caspase inhibitor Z-VAD-FMK confirmed the relevance of late apoptosis for SVA infection, indicating that SVA induces apoptosis, presumably, as a mechanism to facilitate virus release and/or spread from infected cells. Together, these results suggest an important role of apoptosis for SVA infection biology.